Effect of Ureteral Stent Length and Position of Stent Coil in Bladder on Stent-Related Symptoms and Quality of Life of Patients - Mehra, Ketan (Cureus, 2020)
Introduction: Various standardized questionnaires can evaluate ureteral stent-related symptoms. The present study utilized a validated instrument, Ureteral Stent Symptoms Questionnaire (USSQ), to know the impact of the length of double J stent (DJS) in comparison to ureter length on patients and their quality of living. Materials and Method: This study is a prospective clinical study conducted in the Department of Urology at a tertiary care center in South India. Patients who underwent DJS after endoscopic ureteral lithotripsy were included in the study. On a computerized tomography scan, the ureteral to stent length ratio (USR) was calculated. USSQ scores at the time of DJS removal and two weeks thereafter were recorded. The distal coil of the stent in the bladder was recorded as grade 1 - not crossing the midline and grade 2 - crossing the midline. Different symptom scores were compared between both grades of bladder coil and for USR of all the patients. Result: A total of 157 patients were included in the study. Over 46 (29.3%) patients had grade-1 and 111 (70.7%) had grade-2 bladder coil. Totally 93 (59.23%) patients reported pain, while 64 (40.77%) patients had no pain. Grade-2 coil patients had more pain than grade 1 (P=0.01). There was a weak inverse relationship between the USR and urinary symptom (P=0.004), pain symptom (P=0.04), and quality of work (P=0.005). Conclusion: Stent length or position of the intravesical stent coil does not appear to affect the quality of life except for the pain. Hence, choosing stent length according to ureteral length seems to have a minimal role in decreasing stent-related morbidity.